Effect of Interconnection between Cervical Vagus Trunk, Epicardial Fat Pad on Sinus Node Function, and Atrial Fibrillation. Issue 3 (24th September 2013) - ZHOU, QINA; ZHANG, LING; WANG, KUN; XU, XIAOXIA; JI, MENG; ZHANG, FENG; WANG, HONGLI; HOU, YUEMEI
<x xml:space="preserve">Abstract</x> Background The epicardial fat pad (FP) integrates the autonomic innervation between the extrinsic and intrinsic cardiac autonomic nervous system and affects atrial electrophysiology and pathophysiology. Methods Eighteen dogs were divided into two groups: sequential ablation of sinoatrial node FP (SAN‐FP) and atrioventricular node FP (AVN‐FP). Sinus rate (SR), atrial fibrillation (AF) inducibility, and effective refractory period (ERP) changes during electrical stimulation of the vagus trunk were detected before and after ablation. Results In the SAN‐FP group, the SR slowing, increasing AF inducibility, and ERP shortening that induced by vagus trunk stimulation were significantly attenuated by isolated SAN‐FP ablation, compared with the same group prior to ablation (all P < 0.05). Subsequent AVN‐FP ablation following SAN‐FP ablation almost cannot produce further attenuation during vagus trunk stimulation, compared with isolated SAN‐FP ablation (P > 0.05). In the AVN‐FP group, SR slowing, increasing AF inducibility, and ERP shortening that induced by vagus trunk stimulation were completely eliminated by isolated AVN‐FP ablation, compared with the same group prior to ablation (all P < 0.05). Subsequent SAN‐FP ablation following AVN‐FP ablation produced no further attenuation, compared with isolated AVN‐FP ablation (P > 0.05). Conclusions A neural pathway from the cervical vagus trunk to the sinus node and atrium runs through the SAN‐FP, but eventually converges at the AVN‐FP and also suggested that the AVN‐FP serves as an "integration center" for the SAN‐FP to modulate sinus node function. The AVN‐FP may play a more critical role in the initiation and maintenance of AF.